Electric field effect on spectroscopic g-factor and magnetic anisotropy in a Pt/Co/MgO ultrathin film. (1st October 2022) - Mizuno, Hayato; Moriyama, Takahiro; Tanaka, Kensho; Kawaguchi, Masashi; Koyama, Tomohiro; Chiba, Daichi; Ono, Teruo
Abstract: We demonstrate that magnetic crystal anisotropy ( K u ) and spectroscopic g -factor can be modulated simultaneously by gate voltage in a Pt/Co/MgO ultrathin film with our ferromagnetic resonance (FMR) measurement based on the rectification effect. The g -factor reflects on orbital magnetic moment, indicating that the electric field induced-modulations of magnetic anisotropy in cobalt originate from the change of the anisotropy of orbital moments ( ∆ m L ). The quantitative estimation reveals that ∆ m L to K u correlation when the electric field is applied significantly differs from the one inherent at the Pt/Co/MgO interfaces. This means that the correlation itself is also modulated by the electric field. Our results show that the FMR technique is very useful for probing the electric field effect on K u .